Radiation Dose of X-ray and CT Examination in Stomatology - P. Černochová; P. Krupa (Česká Stomatologie a Praktické Zubní Lékařství, 2005)
The patient subjected to X-ray or CT examination is exposed to ionizing radiation. The dose can be measured and calculated by means of various dosimetric units. The effective dose makes it possible to compare radiation load in patients under the use of various imaging methods. The authors present the size of effective dose for CT examination of jaws on spiral CT scanner Marconi Mx8000. The authors also show that there is a possibility to set the values of the examination protocol so as to make the effective dose lower than for the panoramic X-ray picture of the jaws and simultaneously keep sufficient quality of the imaging.